Low-cost high-performance titanium-aluminum intermetallic compound and 3D printing method thereof
By adding Y, Ni and B elements to the titanium-aluminum intermetallic compounds and using 3D printing and vacuum sintering technology, the problems of limited improvement of high-temperature mechanical properties of existing titanium-aluminum intermetallic compounds are solved, and low-cost and high-performance titanium-aluminum intermetallic compounds are achieved to meet the needs of high-temperature structural materials in the fields of aerospace and other fields.
Patent Information
- Application Number
- CN202510087950.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The high-temperature mechanical properties of existing titanium-aluminum intermetallic compounds are limited in their effectiveness and are relatively high in costs, making it difficult to meet market demand.
By adding a small amount of Y, Ni and B elements to the titanium-aluminum intermetallic compound and using 3D printing technology and vacuum sintering process, the adhesive composition and printing process are optimized to improve the high-temperature mechanical properties of the alloy and reduce costs.
It has achieved the preparation of low-cost, high-performance titanium-aluminum intermetallic compounds, and has excellent high-temperature tensile strength, yield strength and elongation after break, meeting the needs of high-temperature structural materials in the fields of aerospace and other fields.
Smart Images

Figure BDA0005251629070000151 
Figure BDA0005251629070000161
Abstract
Description
Technical Field
[0001] The present invention relates to the field of 3D printing technology, and in particular to a low-cost, high-performance titanium-aluminum intermetallic compound and a 3D printing method thereof. Background Art
[0002] Titanium-aluminum intermetallic compounds have an ordered structure and can maintain strength and stiffness at high temperatures. They also have low density, high specific strength, high elastic modulus, good oxidation resistance, good creep properties and excellent fatigue properties. They are high-temperature structural materials that are expected to replace nickel-based high-temperature alloys in aerospace, national defense and military industries, and are therefore widely used in aviation, aerospace, navigation, land transportation and other fields.
[0003] However, the titanium-aluminum intermetallic compounds currently available on the market are mainly composed of titanium and aluminum, and then a small amount of tungsten, molybdenum, niobium and tantalum are introduced to improve their performance. For example, tungsten and molybdenum can improve the oxidation resistance and creep resistance of titanium-aluminum intermetallic compounds at high temperatures, while niobium and tantalum mainly play a role in grain refinement, thereby improving the plasticity of titanium-aluminum intermetallic compounds. However, on the one hand, the above elements are expensive, which greatly increases the cost of titanium-aluminum intermetallic compounds and reduces the market competitiveness of titanium-aluminum intermetallic compounds. On the other hand, the effect of improving the mechanical properties of titanium-aluminum intermetallic compounds is relatively limited, and it is difficult to meet the current market requirements. At the same time, due to the high melting point of tungsten and other elements, it is easy to form element segregation during the preparation process, which further limits the improvement of the high-temperature mechanical properties of titanium-aluminum intermetallic compounds.
[0004] Therefore, providing a titanium-aluminum intermetallic compound with low cost and excellent high-temperature mechanical properties has become a technical problem to be solved urgently in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a low-cost, high-performance titanium-aluminum intermetallic compound and a 3D printing method thereof. The titanium-aluminum intermetallic compound provided by the present invention only introduces a small amount of Y, Ni and B elements, which not only reduces the cost of the alloy, but also the obtained titanium-aluminum intermetallic compound has excellent high-temperature mechanical properties.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a low-cost and high-performance titanium-aluminum intermetallic compound, which comprises, by mass percentage, 0.1-1% Y, 0.1-0.5% Ni, 0.1-0.7% B, 45-53% Ti and the balance Al;
[0008] Among them, the mass ratio of Y, Ni and B satisfies the relationship: Y: (Ni+B)≥0.5.
[0009] Preferably, the titanium-aluminum intermetallic compound comprises, by mass percentage, 0.2-1.0% Y, 0.1-0.4% Ni, 0.2-0.6% B, 46-52% Ti and the balance Al.
[0010] The present invention provides a 3D printing method for a low-cost, high-performance titanium-aluminum intermetallic compound as described in the above technical solution, comprising the following steps:
[0011] (1) mixing titanium-aluminum intermetallic compound powder and a binder to obtain a printing slurry; the composition of the titanium-aluminum intermetallic compound powder is the same as the composition of the titanium-aluminum intermetallic compound described in the above technical solution;
[0012] (2) preparing the printing slurry obtained in step (1) into a printing filament;
[0013] (3) 3D printing the printing filament obtained in step (2) by means of a plastic 3D printer to obtain a 3D printed green body;
[0014] (4) Degreasing the 3D printed green body obtained in step (3) and then vacuum sintering to obtain a titanium-aluminum intermetallic compound.
[0015] Preferably, in step (1), the mixing temperature is 100 to 230° C., the mixing time is 2 to 5 hours, and the mixing method is stirring.
[0016] Preferably, the particle size of the titanium-aluminum intermetallic compound powder in step (1) is 15 to 45 μm.
[0017] Preferably, in terms of mass percentage, the binder in step (1) comprises: 17-35% paraffin, 22-27% stearic acid, 6-8% dimethyl propane, 12-25% polyethylene glycol and the balance polyethylene.
[0018] Preferably, the molecular weight of the polyethylene is 200,000 to 500,000; the molecular weight of the polyethylene glycol is 400 to 600.
[0019] Preferably, the mass percentage of the binder in the printing slurry of step (1) is 5-15%.
[0020] Preferably, the degreasing treatment in step (4) is solvent degreasing and thermal degreasing performed sequentially.
[0021] Preferably, the vacuum degree of vacuum sintering in step (4) is (1-10)×10 -4 Pa, the holding temperature of vacuum sintering is 900-1500℃, and the holding time of vacuum sintering is 0.5-5h.
[0022] The present invention provides a low-cost, high-performance titanium-aluminum intermetallic compound, which comprises, by mass percentage, 0.1-1% Y, 0.1-0.5% Ni, 0.1-0.7% B, 45-53% Ti and the balance Al; wherein the mass ratio of Y, Ni and B satisfies the relationship: Y: (Ni+B)≥0.5. The present invention adds a small amount of Y element to the titanium-aluminum intermetallic compound. During the vacuum sintering process, the Y element can react with the O element in the titanium-aluminum intermetallic compound, thereby playing a role in fixing the O element, which is beneficial to improving the plasticity of the TiAl alloy. The O element reacts with the Y element during the vacuum sintering process to precipitate nano Y2O3 particles. The nano Y2O3 particles can refine the TiAl alloy structure, pin the grain boundaries and hinder the movement of dislocations, thereby further improving the high-temperature mechanical properties of the TiAl alloy. By introducing a small amount of Ni element, the oxidation resistance of the titanium-aluminum intermetallic compound can be improved, thereby making the titanium-aluminum The intermetallic compound has more excellent mechanical properties at high temperature; by adding a small amount of B element, the B element can play a role in refining the grains. On the one hand, it can hinder the movement of dislocations and improve the high-temperature mechanical properties of the titanium-aluminum intermetallic compound. On the other hand, the B element can also reduce the stress concentration caused by dislocation pile-up and improve the toughness of the titanium-aluminum intermetallic compound. At the same time, the refinement of the grains can promote the plastic deformation of the titanium-aluminum intermetallic compound; by controlling the dosage relationship of Y, Ni and B, the Y element and the O element in the titanium-aluminum intermetallic compound can be promoted to form nano Y2O3 particles, thereby further improving the high-temperature mechanical properties of the titanium-aluminum intermetallic compound.
[0023] The present invention adds Y element in the process of preparing titanium-aluminum intermetallic compound, so that the titanium-aluminum intermetallic compound directly contains Y element, which can avoid uneven distribution of Y element in subsequent 3D printing and degreasing process, thereby affecting the mechanical properties of titanium-aluminum intermetallic compound; by using plastic 3D printer for 3D printing, there is no need to use expensive equipment such as laser cladding machine, which greatly reduces the cost of titanium-aluminum intermetallic compound 3D printing equipment, so that 3D printed titanium-aluminum intermetallic compound parts can be more widely used in business; by optimizing the binder, it can be made to have good adhesion and fluidity, ensuring that the slurry can be smoothly printed in the process of 3D printing The material can be laid, and the formed green body structure will not be deformed and has good stability; at the same time, the amount of binder used is small, which can not only further reduce the cost, but also make it easier to remove in the subsequent degreasing treatment, thereby avoiding the degreasing process from affecting the shape of the green body, further improving the printing accuracy of the titanium aluminum intermetallic compound, and improving the qualified rate of the product; by adopting the vacuum sintering method, the oxygen content can be reduced, thereby eliminating the negative impact of the O element in the alloy through the Y element in the alloy, thereby further improving the mechanical properties of the titanium aluminum intermetallic compound; by controlling the temperature and time of vacuum sintering, the density of the titanium aluminum intermetallic compound can be further improved, thereby improving its mechanical properties.
[0024] The results of the examples show that the low-cost, high-performance titanium-aluminum intermetallic compound provided by the present invention has a tensile strength of 610-650 MPa at 800° C., a yield strength of 500-540 MPa, and an elongation after fracture of 11.5-13.5%. DETAILED DESCRIPTION
[0025] The present invention provides a low-cost and high-performance titanium-aluminum intermetallic compound, which comprises, by mass percentage, 0.1-1% Y, 0.1-0.5% Ni, 0.1-0.7% B, 45-53% Ti and the balance Al;
[0026] Among them, the mass ratio of Y, Ni and B satisfies the relationship: Y: (Ni+B)≥0.5.
[0027] The low-cost, high-performance titanium-aluminum intermetallic compound provided by the present invention includes Y in an amount of 0.1-1%, preferably 0.2-1.0%, more preferably 0.4-0.8%, and further preferably 0.6-0.7%, by mass percentage. The present invention adds a small amount of Y element to the titanium-aluminum intermetallic compound, and during the vacuum sintering process, the Y element can react with the O element in the titanium-aluminum intermetallic compound, thereby playing a role in fixing the O element, which is beneficial to improving the plasticity of the TiAl alloy, and the O element reacts with the Y element during the vacuum sintering process to precipitate nano Y2O3 particles, which can refine the structure of the TiAl alloy, pin the grain boundaries and hinder the movement of dislocations, thereby further improving the high-temperature mechanical properties of the TiAl alloy.
[0028] The low-cost, high-performance titanium-aluminum intermetallic compound provided by the present invention includes Ni: 0.1-0.5%, preferably 0.1-0.4%, and more preferably 0.2-0.3%, by mass percentage. The present invention can improve the oxidation resistance of the titanium-aluminum intermetallic compound by introducing a small amount of Ni element, so that the titanium-aluminum intermetallic compound has more excellent mechanical properties at high temperatures.
[0029] The low-cost, high-performance titanium-aluminum intermetallic compound provided by the present invention includes B in an amount of 0.1-0.7%, preferably 0.2-0.6%, more preferably 0.3-0.6%, and further preferably 0.4-0.5%, by mass percentage. The present invention adds a small amount of B element, which can play a role in refining the grains. On the one hand, it can hinder the movement of dislocations and improve the high-temperature mechanical properties of the titanium-aluminum intermetallic compound. On the other hand, the B element can also reduce the stress concentration caused by dislocation pile-up and improve the toughness of the titanium-aluminum intermetallic compound. At the same time, the refinement of the grains can promote the plastic deformation of the titanium-aluminum intermetallic compound.
[0030] The low-cost, high-performance titanium-aluminum intermetallic compound provided by the present invention comprises Ti in an amount of 45-53%, preferably 46-52%, more preferably 46-50%, and further preferably 48-50% by mass. In the present invention, Ti is the matrix material of the titanium-aluminum intermetallic compound.
[0031] The low-cost, high-performance titanium-aluminum intermetallic compound provided by the present invention includes a balance of Al in terms of mass percentage. In the present invention, Al is the matrix material of the titanium-aluminum intermetallic compound.
[0032] In the present invention, the mass ratio of Y, Ni and B satisfies the relationship: Y: (Ni + B) ≥ 0.5, preferably 0.5 to 2, and more preferably 1 to 1.5. The present invention can promote the formation of nano Y2O3 particles by controlling the amount relationship of Y, Ni and B with the O element in the titanium-aluminum intermetallic compound, thereby further improving the high-temperature mechanical properties of the titanium-aluminum intermetallic compound.
[0033] The present invention adds a small amount of Y element to the titanium-aluminum intermetallic compound. During the vacuum sintering process, the Y element can react with the O element in the titanium-aluminum intermetallic compound, thereby effectively reducing the free O element in the alloy, which is beneficial to improving the plasticity of the TiAl alloy. The O element and the Y element react during the vacuum sintering process to precipitate nano Y2O3 particles. The nano Y2O3 particles can refine the TiAl alloy structure, pin the grain boundary and hinder the dislocation movement, thereby further improving the high-temperature mechanical properties of the TiAl alloy. By introducing a small amount of Ni element, the oxidation resistance of the titanium-aluminum intermetallic compound can be improved, thereby making the titanium Aluminum intermetallic compounds have more excellent mechanical properties at high temperatures; by adding a small amount of B element, B element can play a role in refining grains. On the one hand, it can hinder dislocation movement and improve the high-temperature mechanical properties of titanium aluminum intermetallic compounds. On the other hand, B element can also reduce the stress concentration caused by dislocation pile-up and improve the toughness of titanium aluminum intermetallic compounds. At the same time, grain refinement can promote the plastic deformation of titanium aluminum intermetallic compounds; by controlling the dosage relationship of Y, Ni and B, Y element and O element in titanium aluminum intermetallic compounds can be promoted to form nano Y2O3 particles, thereby further improving the high-temperature mechanical properties of titanium aluminum intermetallic compounds.
[0034] The present invention also provides a 3D printing method for the low-cost, high-performance titanium-aluminum intermetallic compound described in the above technical solution, comprising the following steps:
[0035] (1) mixing titanium-aluminum intermetallic compound powder and a binder to obtain a printing slurry; the composition of the titanium-aluminum intermetallic compound powder is the same as the composition of the titanium-aluminum intermetallic compound described in the above technical solution;
[0036] (2) preparing the printing slurry obtained in step (1) into a printing filament;
[0037] (3) 3D printing the printing filament obtained in step (2) by means of a plastic 3D printer to obtain a 3D printed green body;
[0038] (4) Degreasing the 3D printed green body obtained in step (3) and then vacuum sintering to obtain a titanium-aluminum intermetallic compound.
[0039] The invention mixes titanium-aluminum intermetallic compound powder and a binder to obtain printing slurry.
[0040] In the present invention, the composition of the titanium-aluminum intermetallic compound powder is the same as the composition of the titanium-aluminum intermetallic compound described in the above technical solution. The present invention directly adds the Y element to the inside of the titanium-aluminum intermetallic compound powder, rather than adding the Y element separately during the 3D printing process, which can avoid the uneven distribution of the Y element during the subsequent 3D printing and degreasing process, thereby affecting the mechanical properties of the titanium-aluminum intermetallic compound.
[0041] In the present invention, the method for preparing the titanium-aluminum intermetallic compound powder is preferably: firstly mixing Al source, Ti source, Y source, Ni source and B source, smelting to obtain titanium-aluminum intermetallic compound, and then preparing the titanium-aluminum intermetallic compound into titanium-aluminum intermetallic compound powder.
[0042] In the present invention, the Al source is preferably Al powder; the particle size of the Al powder is preferably 100-400 mesh, more preferably 200-300 mesh; the Ti source is preferably Ti powder; the particle size of the Ti powder is preferably 150-300 mesh; the Y source is preferably AlY master alloy or metal Y, more preferably AlY (20%) master alloy; the particle size of the Y source is preferably 80-500 mesh, more preferably 200-350 mesh; the Ni source is preferably AlNi master alloy, more preferably AlNi (20%) master alloy; the particle size of the Ni source is preferably 200-350 mesh; the B source is preferably AlB master alloy, more preferably AlB (20%) master alloy; the particle size of the B source is preferably 150-350 mesh. The present invention has no special restrictions on the specific source of the raw materials, and they can be prepared by commercial products well known to those skilled in the art or by preparation methods well known to those skilled in the art. The present invention has no special restrictions on the specific amount of the raw materials, and the chemical composition of the titanium-aluminum intermetallic compound can meet the technical requirements. The present invention has no particular limitation on the specific mixing method, as long as the Al source, Ti source, Y source, Ni source and B source can be uniformly mixed. As an embodiment of the present invention, the mixing method can be ball milling.
[0043] In the present invention, the smelting method is preferably electron beam selective melting; the process parameters of the electron beam selective melting are preferably: electron beam current 9-13 mA, substrate preheating temperature 1030-1200°C, layer thickness 45-90 μm, serpentine scanning strategy. The present invention can reduce the organizational defects in the titanium aluminum intermetallic compound by using electron beam selective melting to smelt, laying a foundation for the subsequent preparation of titanium aluminum intermetallic compounds with excellent mechanical properties.
[0044] The present invention has no particular limitation on the specific operation of preparing the titanium-aluminum intermetallic compound into the titanium-aluminum intermetallic compound powder, as long as the particle size of the titanium-aluminum intermetallic compound powder meets the requirements. As an embodiment of the present invention, the method of preparing the titanium-aluminum intermetallic compound into the titanium-aluminum intermetallic compound powder can be plasma atomization, electron beam atomization or rotating electrode powder preparation.
[0045] In the present invention, the particle size of the titanium-aluminum intermetallic compound powder is preferably 15 to 45 μm, more preferably 15 to 25 μm. The present invention can improve the compactness of the 3D printed green body by controlling the particle size of the titanium-aluminum intermetallic compound powder, thereby further improving the mechanical properties of the titanium-aluminum intermetallic compound.
[0046] In the present invention, the binder preferably includes, by mass percentage: 17-35% paraffin, 22-27% stearic acid, 6-8% dimethyl propane, 12-25% polyethylene glycol and the balance polyethylene, more preferably: 20-32% paraffin, 24-27% stearic acid, 6-8% dimethyl propane, 15-20% polyethylene glycol and the balance polyethylene; the molecular weight of the polyethylene is preferably 200,000-500,000; the molecular weight of the polyethylene glycol is preferably 400-600. By introducing ethanol and polyethylene glycol into the binder, the present invention can make the binder have good bonding performance and fluidity, and even in the case of a small amount, it will not affect the subsequent 3D printing molding of the printing slurry.
[0047] In the present invention, the mixing temperature is preferably 100 to 230°C; the mixing time is preferably 2 to 5 hours; and the mixing method is preferably stirring. The present invention has no special limitation on the stirring method, and it can be determined according to the technical common sense of those skilled in the art as long as the powder and the binder can be mixed evenly. The present invention can melt the solid components in the binder by controlling the mixing temperature and time, thereby mixing with the metal powder and bonding the metal powder together; by mixing under stirring conditions, the bonding effect can be improved.
[0048] As an embodiment of the present invention, the mixing temperature may be 100°C, 120°C, 150°C, 160°C, 180°C, 200°C or 230°C; the mixing time may be 2h, 3h, 4h or 5h.
[0049] After the mixing is completed, the mixed product is preferably cooled to room temperature. The present invention has no particular limitation on the cooling method and cooling rate, which can be determined according to the technical common sense of those skilled in the art.
[0050] In the present invention, the mass percentage of the binder in the printing slurry is preferably 5-15%. The binder provided by the present invention has good adhesion and fluidity, which can enable the printing slurry to be smoothly laid during the 3D printing process, and the formed green body structure will not be deformed and has good stability; at the same time, the amount of binder is small, which can not only further reduce the cost, but also make it easier to remove in the subsequent degreasing process, thereby avoiding the degreasing process from affecting the shape of the green body, further improving the printing accuracy of the titanium aluminum intermetallic compound, and improving the qualified rate of the product.
[0051] As an embodiment of the present invention, the mass percentage of the binder in the printing slurry can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.
[0052] After obtaining the printing slurry, the present invention prepares the printing slurry into a printing filament.
[0053] In the present invention, the method for preparing the printing slurry into a printing filament is preferably to first prepare a granular feed by a granulator or a crusher, and then use an injection molding machine or a filament making machine to process the granular feed into a printing filament for plastic 3D printing.
[0054] The present invention has no particular limitation on the specific model and source of the granulator and crusher, and commercial products known to those skilled in the art can be used. The present invention has no particular limitation on the parameters in the preparation process, and it only needs to ensure that the size of the granular feed meets the requirements.
[0055] In the present invention, the particle size of the granular feed is preferably ≤5 mm. As an embodiment of the present invention, the particle size of the granular feed can be 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.
[0056] The present invention has no particular limitation on the specific model and source of the injection molding machine or the filament making machine, and commercially available products known to those skilled in the art can be used. The present invention has no particular limitation on the parameters in the preparation process, and it only needs to ensure that the size of the printing filament meets the requirements.
[0057] In the present invention, the length of the printing filament is preferably ≥18 cm; the diameter of the printing filament is preferably 1-4 mm. As an embodiment of the present invention, the length of the printing filament may be 18 cm, 19 cm, 20 cm, 21 cm, 22 cm, 23 cm, 24 cm or 25 cm; the diameter of the printing filament may be 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm or 4 mm.
[0058] After obtaining the printing filament, the present invention performs 3D printing on the printing filament through a plastic 3D printer to obtain a 3D printed green body.
[0059] The present invention does not specifically limit the specific source of the plastic 3D printer, and a commercially available plastic 3D printer familiar to those skilled in the art can be used. As an embodiment of the present invention, the plastic 3D printer preferably adopts a structure in which the print head is fixed during printing, and the workpiece platform can move in the up-down, left-right and / or front-back directions. The present invention uses a plastic 3D printer for 3D printing, eliminating the need for expensive laser cladding machines and other equipment, thereby greatly reducing the cost of titanium-aluminum intermetallic compound 3D printing equipment, allowing 3D printed titanium-aluminum intermetallic compound parts to be more widely used commercially.
[0060] In the present invention, the temperature of the material input end of the print head in the plastic 3D printer during 3D printing is preferably 100-220°C. In the present invention, the temperature of the material input end is preferably controlled by a heater provided on the print head. By controlling the temperature of the material input end, the present invention can avoid the deterioration of the printing effect or even clogging of the printing filament due to cooling and solidification during the transportation process.
[0061] As an embodiment of the present invention, the temperature of the material input end of the print head in the plastic 3D printer during 3D printing may be 100°C, 120°C, 150°C, 160°C, 180°C, 200°C or 220°C.
[0062] In the present invention, the injection nozzle of the injection molding machine or the silk making machine is preferably connected to the material input end of the print head in the plastic 3D printer through a delivery tube; the delivery tube is preferably a metal delivery tube; the delivery tube is preferably heated by a heater; the heating temperature is preferably 100-220°C, more preferably 120-200°C, and further preferably 150-180°C; the heating method is preferably to use an infrared lamp heater or an electric heating tube heater for heating. By adopting the above-mentioned connection method, the present invention can reduce the situation of printing wire breakage during printing, and at the same time avoid cooling and solidification of the printing wire during transportation, thereby further improving the printing effect.
[0063] In the present invention, the print nozzle temperature of the plastic 3D printer is preferably 100-220° C., more preferably 120-200° C., and further preferably 150-180° C. The present invention can avoid the problem of blockage caused by cooling and solidification of the printing filament during the printing process by controlling the print nozzle temperature of the plastic 3D printer.
[0064] The present invention has no special limitation on the specific operation and process parameters of the 3D printing. A three-dimensional model is constructed in a computer according to the shape of the desired titanium-aluminum intermetallic compound, and then the printing parameters are set.
[0065] The present invention preferably performs hot isostatic pressing and surface modification on the product obtained by 3D printing. The present invention has no special limitation on the specific operation of the hot isostatic pressing and surface modification. The hot isostatic pressing and surface modification well known to those skilled in the art can be used to make the size of the 3D printed green body meet the requirements.
[0066] After obtaining the 3D printed green body, the present invention performs a degreasing treatment on the 3D printed green body, and then performs vacuum sintering to obtain a titanium-aluminum intermetallic compound.
[0067] In the present invention, the degreasing treatment preferably includes solvent degreasing and thermal degreasing performed sequentially.
[0068] In the present invention, the solvent degreasing is preferably soaked in a solvent; the solvent is preferably methanol, ethanol, propanol, hexane or trichloroethylene; the temperature of the solvent is preferably 35 to 60°C; the flow rate of the solvent is preferably 3 to 25 cm / s; the time of the solvent degreasing is preferably 2 to 6 hours, more preferably 2 to 4 hours. The present invention can remove part of the soluble binder by performing solvent degreasing.
[0069] After the solvent degreasing is completed, the present invention preferably dries the solvent degreasing product. The present invention has no special limitation on the specific operation of the drying, as long as the solvent can be dried.
[0070] In the present invention, the temperature of the thermal degreasing is preferably 380-900°C, more preferably 450-700°C; the time of the thermal degreasing is preferably 2-4 hours; the atmosphere of the thermal degreasing is preferably an argon atmosphere; the flow rate of the argon is preferably 80-250 L / h, more preferably 180-200 L / h. The present invention performs thermal degreasing in flowing argon, which can remove the gas after the decomposition of the polymer material through the argon gas on the one hand, and prevent the oxygen in the air from reacting with the titanium-aluminum intermetallic compound on the other hand.
[0071] In the present invention, the vacuum degree of the vacuum sintering is preferably (1 to 10)×10 -4 Pa, more preferably (3 to 7)×10 -4 Pa is more preferably (4 to 5)×10 -4 Pa. The present invention can reduce the oxygen content by adopting the vacuum sintering method, thereby eliminating the negative impact of the O element in the alloy through the Y element in the alloy, thereby further improving the mechanical properties of the titanium-aluminum intermetallic compound.
[0072] In the present invention, the holding temperature of the vacuum sintering is preferably 900-1500°C, more preferably 1100-1450°C, and further preferably 1150-1350°C; the holding time of the vacuum sintering is preferably 0.5-5h, more preferably 2-3h; the cooling method of the vacuum sintering is preferably furnace cooling. The present invention can further improve the compactness of the titanium-aluminum intermetallic compound by controlling the temperature and time of vacuum sintering, thereby improving its mechanical properties.
[0073] After obtaining the titanium-aluminum intermetallic compound, the present invention preferably further comprises subjecting the titanium-aluminum intermetallic compound to a shot peening treatment. The present invention has no particular limitation on the specific operation of the shot peening treatment, which can be determined according to the technical common sense of a person skilled in the art. The present invention can improve the surface quality and dimensional accuracy of the titanium-aluminum intermetallic compound by shot peening treatment.
[0074] The present invention adds Y element in the process of preparing titanium-aluminum intermetallic compound, so that the titanium-aluminum intermetallic compound directly contains Y element, which can avoid uneven distribution of Y element in subsequent 3D printing and degreasing process, thereby affecting the mechanical properties of titanium-aluminum intermetallic compound; by using plastic 3D printer for 3D printing, there is no need to use expensive equipment such as laser cladding machine, which greatly reduces the cost of titanium-aluminum intermetallic compound 3D printing equipment, so that 3D printed titanium-aluminum intermetallic compound parts can be more widely used in business; by optimizing the binder, it can be made to have good adhesion and fluidity, ensuring that the slurry can be smoothly printed in the process of 3D printing The material can be laid, and the formed green body structure will not be deformed and has good stability; at the same time, the amount of binder used is small, which can not only further reduce the cost, but also make it easier to remove in the subsequent degreasing treatment, thereby avoiding the degreasing process from affecting the shape of the green body, further improving the printing accuracy of the titanium aluminum intermetallic compound, and improving the qualified rate of the product; by adopting the vacuum sintering method, the oxygen content can be reduced, thereby eliminating the negative impact of the O element in the alloy through the Y element in the alloy, thereby further improving the mechanical properties of the titanium aluminum intermetallic compound; by controlling the temperature and time of vacuum sintering, the density of the titanium aluminum intermetallic compound can be further improved, thereby improving its mechanical properties.
[0075] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0076] Example 1
[0077] A low-cost, high-performance titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.8%, Ni: 0.3%, B: 0.1%, Ti: 48% and the balance Al;
[0078] The mass ratio of Y: (Ni+B) is 2;
[0079] The 3D printing method of the low-cost and high-performance titanium-aluminum intermetallic compound is:
[0080] (1) A titanium-aluminum intermetallic compound powder and a binder are stirred and mixed at 180° C. for 4 hours to obtain a printing slurry; the preparation method of the titanium-aluminum intermetallic compound powder is: Al powder, Ti powder, AlY (20%) master alloy, AlNi (20%) master alloy and AlB (20%) master alloy are ball-milled and mixed, and then electron beam selective melting is performed to obtain a titanium-aluminum intermetallic compound, and then the titanium-aluminum intermetallic compound is prepared into a titanium-aluminum intermetallic compound powder with a particle size of 15 to 63 μm by a plasma atomization method; Al powder, Ti powder, AlY (20%) master alloy are mixed, and AlB (20%) master alloy is mixed, and then electron beam selective melting is performed to obtain a titanium-aluminum intermetallic compound. The particle sizes of gold, AlNi (20%) master alloy and AlB (20%) master alloy are independently 250 meshes; the process parameters of the electron beam selective melting are: electron beam current 11mA, substrate preheating temperature 1120°C, layer thickness 57μm, serpentine scanning strategy; in terms of mass percentage, the binder is: paraffin 32%, stearic acid 22%, dimethyl propane 6%, polyethylene glycol 15% and the balance polyethylene, the molecular weight of polyethylene is 200,000 to 500,000, and the molecular weight of polyethylene glycol is 400 to 600; the mass percentage of the binder in the printing slurry is 10%;
[0081] (2) The printing slurry obtained in step (1) is first prepared into a granular feed by a granulator, and then the granular feed is processed into a printing filament for plastic 3D printing by an injection molding machine; the particle size of the granular feed is 3 to 5 mm; the length of the printing filament is 18 to 20 cm, and the diameter of the printing filament is 1 to 4 mm;
[0082] (3) constructing a three-dimensional model in a computer, and then performing 3D printing on the printing filament obtained in step (2) through a metal conveying tube and a plastic 3D printer to obtain a 3D printed green body; during the printing process of the plastic 3D printer, a structure is adopted in which the print head is fixed and the workpiece platform can move in the up-down, left-right and / or front-back directions, and the injection nozzle of the injection molding machine is connected to the material input end of the print head in the plastic 3D printer; the metal conveying tube is heated to 180° C. by an infrared lamp heater; during the 3D printing, the temperature of the material input end of the print head in the plastic 3D printer is 180° C., and the temperature of the print nozzle of the plastic 3D printer is 180° C.;
[0083] (4) The 3D printed green body obtained in step (3) is subjected to solvent degreasing, drying and thermal degreasing in sequence, and then vacuum sintering and shot peening to obtain a titanium aluminum intermetallic compound; the solvent degreasing is performed by immersing in ethanol, the temperature of the solvent degreasing is 45° C., the flow rate of ethanol is 15 cm / s, and the solvent degreasing treatment time is 2.5 h; the temperature of the thermal degreasing is 650° C., the thermal degreasing time is 2 h, the atmosphere of the thermal degreasing is an argon atmosphere, and the flow rate of argon is 180 L / h; the vacuum degree of the vacuum sintering is 5×10 -4 Pa, the holding temperature of vacuum sintering is 1200℃, the holding time of vacuum sintering is 2h, and the cooling method of vacuum sintering is furnace cooling.
[0084] Example 2
[0085] A low-cost, high-performance titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.9%, Ni: 0.3%, B: 0.3%, Ti: 48% and the balance Al;
[0086] The mass ratio of Y: (Ni+B) is 1.5;
[0087] The 3D printing method of the low-cost, high-performance titanium-aluminum intermetallic compound is the same as that in Example 1.
[0088] Example 3
[0089] A low-cost, high-performance titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.8%, Ni: 0.4%, B: 0.4%, Ti: 48% and the balance Al;
[0090] The mass ratio of Y: (Ni+B) is 1;
[0091] The 3D printing method of the low-cost, high-performance titanium-aluminum intermetallic compound is the same as that in Example 1.
[0092] Example 4
[0093] A low-cost, high-performance titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.6%, Ni: 0.5%, B: 0.7%, Ti: 48% and the balance Al;
[0094] The mass ratio of Y: (Ni+B) is 0.5;
[0095] The 3D printing method of the low-cost, high-performance titanium-aluminum intermetallic compound is the same as that in Example 1.
[0096] Example 5
[0097] The mass percentage of the binder in the printing slurry in step (1) is 6%, and other conditions are the same as those in Example 1.
[0098] Example 6
[0099] The mass percentage of the binder in the printing slurry in step (1) is 8%, and other conditions are the same as those in Example 1.
[0100] Example 7
[0101] The mass percentage of the binder in the printing slurry in step (1) is 12%, and other conditions are the same as those in Example 1.
[0102] Example 8
[0103] The mass percentage of the binder in the printing slurry in step (1) is 15%, and other conditions are the same as those in Example 1.
[0104] Comparative Example 1
[0105] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Ni: 0.3%, B: 0.1%, Ti: 48% and the balance Al;
[0106] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that in Example 1.
[0107] Comparative Example 2
[0108] A titanium-aluminum intermetallic compound, which comprises, by mass percentage, 0.3% Ni, 0.3% B, 48% Ti and the balance Al;
[0109] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that in Example 2.
[0110] Comparative Example 3
[0111] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Ni: 0.4%, B: 0.4%, Ti: 48% and the balance Al;
[0112] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that in Example 3.
[0113] Comparative Example 4
[0114] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Ni: 0.5%, B: 0.7%, Ti: 48% and the balance Al;
[0115] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that in Example 4.
[0116] Comparative Example 5
[0117] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.8%, Ni: 0.3%, B: 0.1%, Ti: 48% and the balance Al;
[0118] The mass ratio of Y: (Ni+B) is 2;
[0119] The 3D printing method of the low-cost and high-performance titanium-aluminum intermetallic compound is:
[0120] (1) A titanium-aluminum intermetallic compound powder, an AlY (20%) master alloy and a binder are stirred and mixed at 180° C. for 4 hours to obtain a printing slurry; the preparation method of the titanium-aluminum intermetallic compound powder is as follows: Al powder, Ti powder, AlNi (20%) master alloy and AlB (20%) master alloy are ball-milled and mixed, and then electron beam selective melting is performed to obtain a titanium-aluminum intermetallic compound, and then the titanium-aluminum intermetallic compound is prepared into a titanium-aluminum intermetallic compound powder with a particle size of 15 to 63 μm by a plasma atomization method; Al powder, Ti powder, AlNi The particle sizes of the Al(20%) master alloy and the AlB(20%) master alloy are independently 250 meshes; the process parameters of the electron beam selective melting are: electron beam current 11mA, substrate preheating temperature 1120°C, layer thickness 57μm, serpentine scanning strategy; in terms of mass percentage, the binder is: paraffin 32%, stearic acid 22%, dimethyl propane 6%, polyethylene glycol 15% and the balance polyethylene, the molecular weight of polyethylene is 200,000 to 500,000, and the molecular weight of polyethylene glycol is 400 to 600; the mass percentage of the binder in the printing slurry is 10%;
[0121] (2) The printing slurry obtained in step (1) is first prepared into a granular feed by a granulator, and then the granular feed is processed into a printing filament for plastic 3D printing by an injection molding machine; the particle size of the granular feed is 3 to 5 mm; the length of the printing filament is 18 to 20 cm, and the diameter of the printing filament is 1 to 4 mm;
[0122] (3) constructing a three-dimensional model in a computer, and then performing 3D printing on the printing filament obtained in step (2) through a metal conveying tube and a plastic 3D printer to obtain a 3D printed green body; during the printing process of the plastic 3D printer, a structure is adopted in which the print head is fixed and the workpiece platform can move in the up-down, left-right and / or front-back directions, and the injection nozzle of the injection molding machine is connected to the material input end of the print head in the plastic 3D printer; the metal conveying tube is heated to 180° C. by an infrared lamp heater; during the 3D printing, the temperature of the material input end of the print head in the plastic 3D printer is 180° C., and the temperature of the print nozzle of the plastic 3D printer is 180° C.;
[0123] (4) The 3D printed green body obtained in step (3) is subjected to solvent degreasing, drying and thermal degreasing in sequence, and then vacuum sintering and shot peening to obtain a titanium aluminum intermetallic compound; the solvent degreasing is performed by immersing in ethanol, the temperature of the solvent degreasing is 45° C., the flow rate of ethanol is 15 cm / s, and the solvent degreasing treatment time is 2.5 h; the temperature of the thermal degreasing is 650° C., the thermal degreasing time is 2 h, the atmosphere of the thermal degreasing is an argon atmosphere, and the flow rate of argon is 180 L / h; the vacuum degree of the vacuum sintering is 5×10 -4 Pa, the holding temperature of vacuum sintering is 1200℃, the holding time of vacuum sintering is 2h, and the cooling method of vacuum sintering is furnace cooling.
[0124] Comparative Example 6
[0125] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.9%, Ni: 0.3%, B: 0.3%, Ti: 48% and the balance Al;
[0126] The mass ratio of Y: (Ni+B) is 1.5;
[0127] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that of Comparative Example 5.
[0128] Comparative Example 7
[0129] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.8%, Ni: 0.4%, B: 0.4%, Ti: 48% and the balance Al;
[0130] The mass ratio of Y: (Ni+B) is 1;
[0131] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that of Comparative Example 5.
[0132] Comparative Example 8
[0133] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.6%, Ni: 0.5%, B: 0.7%, Ti: 48% and the balance Al;
[0134] The mass ratio of Y: (Ni+B) is 0.5;
[0135] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that of Comparative Example 5.
[0136] Comparative Example 9
[0137] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.8%, Ni: 0.3%, B: 0.1%, Ti: 48% and the balance Al;
[0138] The mass ratio of Y: (Ni+B) is 2;
[0139] (1) A titanium-aluminum intermetallic compound powder and a binder are stirred and mixed at 220° C. for 4 hours to obtain a printing slurry; the preparation method of the titanium-aluminum intermetallic compound powder is: Al powder, Ti powder, AlY (20%) master alloy, AlNi (20%) master alloy and AlB (20%) master alloy are ball-milled and mixed, and then electron beam selective melting is performed to obtain a titanium-aluminum intermetallic compound, and then the titanium-aluminum intermetallic compound is prepared into a titanium-aluminum intermetallic compound powder with a particle size of 15 to 63 μm by a plasma atomization method; Al The particle sizes of Ti powder, Ti powder, AlY (20%) master alloy, AlNi (20%) master alloy and AlB (20%) master alloy are independently 250 mesh; the process parameters of the electron beam selective melting are: electron beam current 11mA, substrate preheating temperature 1120°C, layer thickness 57μm, serpentine scanning strategy; in terms of mass percentage, the binder is: paraffin 42%, stearic acid 30% and the balance polyethylene, the molecular weight of polyethylene is 200,000 to 500,000; the mass percentage of the binder in the printing slurry is 32%;
[0140] (2) The printing slurry obtained in step (1) is first prepared into a granular feed by a granulator, and then the granular feed is processed into a printing filament for plastic 3D printing by an injection molding machine; the particle size of the granular feed is 3 to 5 mm; the length of the printing filament is 18 to 20 cm, and the diameter of the printing filament is 1 to 4 mm;
[0141] (3) constructing a three-dimensional model in a computer, and then performing 3D printing on the printing filament obtained in step (2) through a metal conveying tube and a plastic 3D printer to obtain a 3D printed green body; during the printing process of the plastic 3D printer, a structure is adopted in which the print head is fixed and the workpiece platform can move in the up-down, left-right and / or front-back directions, and the injection nozzle of the injection molding machine is connected to the material input end of the print head in the plastic 3D printer; the metal conveying tube is heated to 180° C. by an infrared lamp heater; during the 3D printing, the temperature of the material input end of the print head in the plastic 3D printer is 180° C., and the temperature of the print nozzle of the plastic 3D printer is 180° C.;
[0142] (4) The 3D printed green body obtained in step (3) is subjected to solvent degreasing, drying and thermal degreasing in sequence, and then vacuum sintering and shot peening to obtain a titanium aluminum intermetallic compound; the solvent degreasing is performed by immersing in ethanol, the temperature of the solvent degreasing is 45° C., the flow rate of ethanol is 15 cm / s, and the solvent degreasing treatment time is 2.5 h; the temperature of the thermal degreasing is 650° C., the thermal degreasing time is 2 h, the atmosphere of the thermal degreasing is an argon atmosphere, and the flow rate of argon is 180 L / h; the vacuum degree of the vacuum sintering is 5×10-4 Pa, the holding temperature of vacuum sintering is 1200℃, the holding time of vacuum sintering is 2h, and the cooling method of vacuum sintering is furnace cooling.
[0143] Comparative Example 10
[0144] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.9%, Ni: 0.3%, B: 0.3%, Ti: 48% and the balance Al;
[0145] The mass ratio of Y: (Ni+B) is 1.5;
[0146] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that of Comparative Example 9.
[0147] Comparative Example 11
[0148] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.8%, Ni: 0.4%, B: 0.4%, Ti: 48% and the balance Al;
[0149] The mass ratio of Y: (Ni+B) is 1;
[0150] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that of Comparative Example 9.
[0151] Comparative Example 12
[0152] A titanium-aluminum intermetallic compound, which, by mass percentage, comprises: Y: 0.6%, Ni: 0.5%, B: 0.7%, Ti: 48% and the balance Al;
[0153] The mass ratio of Y: (Ni+B) is 0.5;
[0154] The 3D printing method of the titanium-aluminum intermetallic compound is the same as that of Comparative Example 9.
[0155] The properties of the titanium-aluminum intermetallic compounds obtained in Examples 1 to 8 and Comparative Examples 1 to 12 were tested, and the results are shown in Table 1:
[0156] Table 1 Properties of titanium-aluminum intermetallic compounds obtained in Examples 1 to 8 and Comparative Examples 1 to 12
[0157]
[0158]
[0159] Among them, the tensile strength test standard is GBT228-1987 Metal Tensile Test Method;
[0160] The yield strength test standard is GBT228-1987 Metal Tensile Test Method;
[0161] The elongation after fracture test standard is GBT228-1987 metal tensile test method.
[0162] Table 1 is analyzed. It can be seen from the data changes of Examples 1 to 4 in Table 1 that with the changes in the contents of the three elements Y, Ni and B in the titanium-aluminum intermetallic compound, the high-temperature mechanical properties of the titanium-aluminum intermetallic compound change, but the overall change range is small; it can be seen from the performance changes of Examples 1 to 4 and Comparative Examples 1 to 4 that when the addition of the Y element to the titanium-aluminum intermetallic compound is omitted, the high-temperature tensile strength and yield strength of the titanium-aluminum intermetallic compound decrease significantly, and the elongation after fracture also decreases significantly, indicating that the present invention is beneficial to improving the plasticity of the TiAl alloy and improving the high-temperature mechanical properties of the TiAl alloy by adding a small amount of Y element to the titanium-aluminum intermetallic compound.
[0163] It can be seen from the performance changes of Examples 1 to 4 and Comparative Examples 5 to 8 that when the Y element is added alone in the form of an AlY intermediate alloy, the high-temperature tensile strength, yield strength and elongation at break of the prepared titanium-aluminum intermetallic compound all show a downward trend. It is found through analysis that during the degreasing treatment and vacuum sintering process, the Y element is unevenly distributed in the titanium-aluminum intermetallic compound, which leads to a decrease in the mechanical properties and plasticity of the titanium-aluminum intermetallic compound. This shows that the addition of the Y element to the titanium-aluminum intermetallic compound powder in the present invention can significantly improve the distribution uniformity of the Y element, thereby further improving the high-temperature performance of the TiAl alloy.
[0164] By comparing Example 1, Examples 5 to 8 and Comparative Examples 9 to 12, it can be seen that when ethanol and polyethylene glycol are omitted from the binder, although the overall performance of the TiAl alloy decreases less, the amount of binder required in the process of preparing the green body is greatly increased, indicating that the present invention can significantly reduce the amount of the binder by optimizing the binder, thereby reducing the production cost of titanium aluminum intermetallic compounds.
[0165] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low-cost, high-performance titanium-aluminum intermetallic compound, comprising, by mass percentage: Y: 0.1~1%, Ni: 0.1~0.5%, B: 0.1~0.7%, Ti: 45~53% and the balance Al; Among them, the mass ratio of Y, Ni and B satisfies the relationship: Y: (Ni+B)≥0.
5.
2. The titanium-aluminum intermetallic compound according to claim 1, characterized in that Calculated by mass percentage, it includes: Y: 0.2-1.0%, Ni: 0.1-0.4%, B: 0.2-0.6%, Ti: 46-52% and the balance Al.
3. The 3D printing method of low-cost, high-performance titanium-aluminum intermetallic compound according to any one of claims 1 to 2, comprising the following steps; (1) mixing titanium-aluminum intermetallic compound powder and a binder to obtain a printing paste; the composition of the titanium-aluminum intermetallic compound powder is the same as the composition of the titanium-aluminum intermetallic compound according to any one of claims 1 to 2; (2) preparing the printing slurry obtained in step (1) into a printing filament; (3) 3D printing the printing filament obtained in step (2) by means of a plastic 3D printer to obtain a 3D printed green body; (4) Degreasing the 3D printed green body obtained in step (3) and then vacuum sintering to obtain a titanium-aluminum intermetallic compound.
4. The 3D printing method according to claim 3, characterized in that: The mixing temperature in step (1) is 100-230° C., the mixing time is 2-5 hours, and the mixing method is stirring.
5. The 3D printing method according to claim 3, characterized in that: The particle size of the titanium-aluminum intermetallic compound powder in step (1) is 15 to 45 μm.
6. The 3D printing method according to claim 3, characterized in that: Calculated by mass percentage, the binder in step (1) comprises: 17-35% paraffin, 22-27% stearic acid, 6-8% dimethyl propane, 12-25% polyethylene glycol and the balance polyethylene.
7. The 3D printing method according to claim 6, characterized in that: The molecular weight of the polyethylene is 200,000 to 500,000; the molecular weight of the polyethylene glycol is 400 to 600.
8. The 3D printing method according to claim 3, characterized in that: The mass percentage of the binder in the printing slurry of step (1) is 5-15%.
9. The 3D printing method according to claim 3, characterized in that: The degreasing treatment in step (4) is solvent degreasing and thermal degreasing performed sequentially.
10. The 3D printing method according to claim 3, characterized in that: The vacuum degree of the vacuum sintering in step (4) is (1-10)×10 -4 Pa, the holding temperature of vacuum sintering is 900-1500℃, and the holding time of vacuum sintering is 0.5-5h.